PERBEDAAN EFEKTIVITAS MODEL PEMBELAJARAN STUDENT TEAMS ACHIVEMENT DIVISION (STAD) DAN NUMBER HEAD TOGETHER (NHT) - Fathoni Candra Kurniawan; Sulastri Sulastri (Universitas Negeri Malang, 2014)
This research aims to examine the effectivity of student teams achievement division (STAD) learning model and number head together (NHT) learning model to increase accounting student achievement. Data was gathered by pretest and postest. Data analysis used independent sample t-test. The result show that (1) student achievement using student teams achievement division (STAD) learning model and number head together (NHT) have increased and (2) there are differences between STAD and NHT learning model increasing accounting student achievement.